Large bowel hernia: pathology and clinic - Croci, Fabio; Suiffet, Walter (Cirugía del Uruguay, 1984)
Inguinal t,erniai; gf the large bowel constitute a not frequent variety of hernia, inter¡¡sting fron the patholQ, gical point of view_ ¡md a controversia! su!:>jetct as tQ §urgical tFeatment. E!ased on their per§onal experien, ce, acquireq through the operation of fjfty large bowel sliding hernias the authors analyze the pathogenic1 anatomo-pathological, clinic and evolutive